2014
DOI: 10.1371/journal.pone.0106306
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Variants of a β-Glucosidase Secreted by a Taiwanese Fungus, Chaetomella raphigera, Exhibit Variant-Specific Catalytic and Biochemical Properties

Abstract: Cellulosic biomass is an abundant and promising energy source. To make cellulosic biofuels competitive against conventional fuels, conversion of rigid plant materials into sugars must become efficient and cost-effective. During cellulose degradation, cellulolytic enzymes generate cellobiose (β-(1→4)-glucose dimer) molecules, which in turn inhibit such enzymes by negative feedback. β-Glucosidases (BGLs) cleave cellobiose into glucose monomers, assisting overall cellulolytic activities. Therefore, BGLs are essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…This observation is consistent with our previous findings that Pichia pastoris -produced recombinant D2-BGL activity was sensitive to SDS and could not be renatured even after SDS was removed [ 30 ]. This finding is likely to due to unusual glycosylation of this enzyme in Pichia [ 30 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with our previous findings that Pichia pastoris -produced recombinant D2-BGL activity was sensitive to SDS and could not be renatured even after SDS was removed [ 30 ]. This finding is likely to due to unusual glycosylation of this enzyme in Pichia [ 30 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…This phenomenon has been observed in many cases. Previous studies have shown that the C. raphigera expressed native D2-BGL has two glycosylation variants and the more extensively O -glycosylated form exhibited increased activity toward its natural substrate cellobiose [ 30 ]. The recombinant A. aculeatus Aa BGL1, a 91-kDa β-glucosidase with 16 potential N -glycosidation sites, showed a smeared band between 135 and 140 kDa during SDS-PAGE analysis [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, N-glycosylation is essential for proper protein folding and the secretion of recombinant Aspergillus terreus β-glucosidase [43], whereas O-glycosylation decreases pH stability of T. leycettanus β-glucosidase [39]. In our previous study [27], we observed that C. raphigera -expressed native D2-BGL has two glycosylation variants, and the large-form native D2-BGL with greater O-glycosylation showed higher enzyme activity toward cellobiose. For P. pastoris -expressed D2-BGL, both N-glycosylation and O-glycosylation may function in enzyme stability and secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Cloning of D2-BGL cDNA into pGAPZαC vector (Invitrogen, USA) was performed as described [27] to generate the expression vector Pp D2-BGL #1. To increase purification yield by affinity chromatography, a second vector ( Pp D2-BGL #5) was generated by inserting an additional 6-histidine tag at the N terminus of D2-BGL.…”
Section: Methodsmentioning
confidence: 99%
“…raphigera was reported to produce pectinase, cellulase and xylanase activity, which could play a major virulence role for rot in pomegranates [41]. Yoneda et al [42] reported that β-glucosidase secreted by C . raphigera .…”
Section: Discussionmentioning
confidence: 99%